Estudo químico e farmacológico de plantas do nordeste dos gêneros Senna e Chamaecrista: desreplicação e ensaios In Silico - Oliveira, Ana Paula Saraiva de (2023)
The plants of Senna and Chamaecrista genus are a source of several compounds with anticancer, anti-inflammatory, and antiviral effects, such as flavonoids, anthraquinones and terpenes. The investigation of their medicinal properties by the combination of experimental and in silico methods brings a more complete knowledge of the potentialities and means of action, valuing the composition of the genus and increasing the confidence for the use of medicinal plants in the treatment of diseases. The classic phytochemistry using HPLC-ESI-MS and HPLC-DAD enabled the identification of twenty-eight (28) compounds in the ethanolic extracts of aerial parts from Senna cearensis Afr.Fern and Senna pendula I&B. The chromatographic fractionation of the fruits and leaves of Senna cearensis and analysis of their LC-MS results by molecular network provided the identification of additional glycosylated compounds and organic acids. The compounds luteolin-7-O-β-rutinoside and cassiaflavan-(4β→8)-epicatechin were isolated for in the Senna pendula leaves extract, with unequivocally identification by mass spectrometry and hydrogen and carbon nuclear magnetic resonance. The cytotoxic effect of the extracts was tested against tumoral cell lines, with the best results of antitumor activity for the extracts of the leaves and fruits of Senna cearensis. In the study of Chamaecrista genus¸ online tools of medicinal chemistry were used for predicting the physico-chemical and pharmacokinetic properties of 164 compounds identified in eight (08) species of the genus. Based on the predicted properties, four flavonoids (apigenin, fisetin, luteolin, and ononin) were submitted to molecular docking and molecular dynamics simulations with DNA (PDB ID:1BNA). The molecular docking verified that ononin have higher affinity with B-DNA, with an ΔG value of -9,3 kcal.mol-1, compared to the other flavonoids. The molecular dynamics simulations of the complex flavonoid-DNA showed that the flavonoids interacted with the DNA by hydrogen bonds, hydrophobic interactions and π stacking. The study of the species de S. cearensis and S. pendula enhances the data about the diversity of the species and increases their applicability. The properties obtained in the in silico studies testified the drug-like potential of compounds found in the species of Chamaecrista genus and provide an overview of how rich the composition of the species from this genus are.